Use of apheresis in the age of new therapies for familial hypercholesterolaemia. Issue 6 (December 2021) - Thompson, Gilbert R.
Abstract : Purpose of review: Lipoprotein apheresis has been first line therapy for homozygous familial hypercholesterolaemia (FH) and other severe and refractory forms of dyslpidaemia for over 40 years but the recent advent of novel and potent LDL-lowering compounds necessitates a reappraisal of its role. Recent findings: During the past decade a substantial amount of evidence has accumulated describing the effect of LDL-lowering with apheresis and conventional drug therapy upon the cardiovascular outcomes associated with homozygous and statin-refractory heterozygous FH. This has necessitated re-defining the target levels of LDL cholesterol needed to arrest progression of atherosclerosis in these situations. At the same time, evidence has accrued regarding the pathogenicity of raised levels of lipoprotein (a) and the promising role of apheresis in mitigating the adverse effects of the latter. The latest advance in treatment has been the introduction of three classes of novel and potent LDL-lowering compounds in the shape of inhibitors of Propertin convertase subtilisin kexin 9 (PCSK9), microsomal triglyceride transfer protein and angiopoietin-like 3. Summary: These recent developments raise the question of whether these compounds will be used as adjuvants to bolster lipoprotein apheresis in FH homozygotes or whether they will render it obsolete, as is already occurring with PCSK9 inhibitors in FH heterozygotes.